A contribution to economic geography of Slovenia - Drozg, Vladimir (Journal for Geography, 2007)
The contribution shows the chosen spatial characteristics of the economic structure of Slovenia in a narrative way, namely: phases of economic development, spatial pattern that occurred in individual phases, decrease of importance of agriculture, gradual deindustrialization, tertiarization, transition of economy after the year 1990, towns as economic centers and regional disparities in economic development of statistical regions.